2012
DOI: 10.1039/c2cp23602h
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state dynamics and efficient triplet formation in phenylthiophene compounds

Abstract: Ultrafast transient absorption spectroscopy monitors the solution-phase dynamics of 2-phenylthiophene (PT), 2-methyl-5-phenylthiophene (MPT), and 2,4-dimethyl-5-phenylthiophene (DMPT) following excitation to the first singlet excited state. Rapid spectral evolution indicates that structural relaxation on the S(1) potential energy surface occurs within ~100 fs, whereas the picosecond-scale kinetics reveal efficient intersystem crossing to the triplet manifold of states. The rate of intersystem crossing is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…We measure TA spectra for both parallel and perpendicular polarization, then calculate the isotropic spectra, DA iso ¼ (DA k + 2DA t )/3, in order to eliminate contributions from rotational reorientation. 41 Independently, we measure the trans / cis photoisomerization quantum yields (F t/c ) for pp* excitation by monitoring the change in transmission of 320 nm laser pulses through a solution of the trans isomer in a static 1 mm cuvette. 42,43 In order to account for small shot-to-shot uctuations of the laser, we use a 50% beam splitter to separate the UV laser light into signal and reference beams before the sample, then simultaneously measure the intensity of the two beams with identical integrating photodiodes operating at 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…We measure TA spectra for both parallel and perpendicular polarization, then calculate the isotropic spectra, DA iso ¼ (DA k + 2DA t )/3, in order to eliminate contributions from rotational reorientation. 41 Independently, we measure the trans / cis photoisomerization quantum yields (F t/c ) for pp* excitation by monitoring the change in transmission of 320 nm laser pulses through a solution of the trans isomer in a static 1 mm cuvette. 42,43 In order to account for small shot-to-shot uctuations of the laser, we use a 50% beam splitter to separate the UV laser light into signal and reference beams before the sample, then simultaneously measure the intensity of the two beams with identical integrating photodiodes operating at 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Such a relationship is well-known and supported by recent work with substituted phenylthiophenes that has demonstrated that ISC rates are directly sensitive to torsional dihedral angle. 62 The ISC lifetime measured for PCMT is somewhat shorter than that of 2T in solution, further suggesting that the effective delocalization length of the relaxed exciton in PCMT is on the order of 2-3 monomer units. More importantly, the substantially faster rate relative to other polythiophenes reflects that the relative energetics and/or coupling between singlet and triplet manifolds are highly sensitive to the torsional dihedral angle.…”
Section: B Intersystem Crossing In Pcmtmentioning
confidence: 95%
“…Two-beam PP experiments follow the usual techniques for shot-to-shot detection. 44 Three-beam PReP experiments use two choppers, one in each of the pump beams. One chopper operates at 500 Hz to block alternating laser pulses, whereas the other chopper operates at 250 Hz and blocks two successive pulses to obtain all four possible combinations of pump pulses (on−on, on−off, off−on, and off−off).…”
mentioning
confidence: 99%